Confronting Challenges and Proposed Solutions for the Sudan Immunization Program Amid Ongoing Armed Conflict - Muaath A. Mohammed; Ibrahim A. Ali; Nazik Elmalaika Husain (Sudan Journal of Medical Sciences, 2023)
Abstract